Signalling via CD28 of human naive neonatal T lymphocytes. - O'NEILL, LUKE ANTHONY JOHN (British Society for Immunology, 1995)
Accessory molecules play a crucial role in the development of the T cell response to antigenic challenge. We have examined the role of CD28 in modulating the 'naive' neonatal T cell response to anti-CD2-mediated activation. To compare the role of CD28, neonatal and adult T cells were stimulated with a pair of mitogenic anti-CD2 antibodies in the presence or absence of anti-CD28 MoAb. With anti-CD2 alone, neonatal T cells proliferated slightly but produced no detectable IL-2, whereas adult T cells proliferated vigorously, with significant IL-2 production. Costimulation with anti-CD28 MoAb greatly enhanced the proliferative response of neonatal T cells to levels equivalent to those of adult T cells, whereas adult T cells showed only slight increases. Although IL-2 secretion was increased in the presence of anti-CD28 MoAb, neonatal T cell IL-2 production remained lower than in adults. In contrast, enhancement of IL-2 mRNA expression in neonates was similar to adult levels. Anti-CD28 MoAb costimulation increased NF kappa B levels in neonates, albeit to levels lower than that of adults. The cellular mechanism governing the diminished proliferative response of neonatal T lymphocytes to anti-CD2 may therefore be due to decreased NF kappa B induction, reduced IL-2 mRNA expression and deficient IL-2 production. Although anti-CD28 MoAb costimulation enhances all of the above signals, NF kappa B and IL-2 levels remain lower than in adults, suggesting the need for further activation requirements in the neonate.
PUBLISHED
Keywords: neonatal T cells CD28 IL-2 mRNA NFKB